Depression influences the quality of diabetes-related self-management activities in elderly patients with type 2 diabetes: a cross-sectional study - Mut-Vitcu G (Dove Medical Press, 2016)
Gabriela Mut-Vitcu,1 Bogdan Timar,2 Romulus Timar,1 Cristian Oancea,3 Ioan Cosmin Citu4 1Second Department of Internal Medicine, 2Department of Functional Sciences, 3Department of Infectious Diseases, 4Department of Obstetrics and Gynecology, “Victor Babes” University of Medicine and Pharmacy, Timisoara, Romania Purpose: To evaluate the prevalence of depression and its impact on the quality of diabetes-related self-care activities in elderly patients with type 2 diabetes. Patients and methods: In this cross-sectional study, 184 patients with type 2 diabetes were enrolled. Depression was evaluated using Patient Health Questionnaire-9 while the quality of diabetes-related self-care activities was assessed using the Summary of Diabetes-Related Self Care Activities Questionnaire. Results: In our study group, 53.3% of the patients had moderate depression, 17.9% had severe depression, and 28.8% had no depression symptoms. Patient’s age (P=0.024), presence of diabetic neuropathy (P<0.001), and body mass index (P=0.037) proved to be independent and significant predictors for developing depression in patients with type 2 diabetes. The severity of depression was reverse correlated with the quality of self-care activities for all the studied components: global score (r=-0.305), diet intervention score (r=-0.297), exercise score (r=-0.388), glycemic monitoring score (r=-0.055), and feet care score (r=-0.180). The presence of severe depression was associated with an increased prevalence of diabetes complications such as diabetic neuropathy and chronic kidney disease. Conclusion: The prevalence of depression is higher in patients with type 2 diabetes compared to general population. Depression has a major negative impact on the quality of diabetes-related self-care activities and, being a treatable condition, proactive screening followed in case of a positive diagnosis by adequate treatment should be performed in all patients with diabetes. Keywords: diabetes, depression, self-care, quality of life